Microbial enzyme activity and stoichiometry signal the effects of agricultural intervention on nutrient cycling in peatlands. (March 2021) - Qin, Lei; Freeman, Chris; Jia, Xueying; Zhang, Zhongsheng; Liu, Bo; Zhang, Shaoqing; Jiang, Ming
Highlights: Large carbon loss and phosphorus accumulation occur in agricultural utilized peatlands. N and P were more abundant at the surface of disturbed peatlands than the subsoil. Increased total P has negative effect on both N-acetyl-β-glucosaminidase and phosphatase. Total P and soil organic carbon explain most of the variance of soil enzymatic activity and stoichiometry. Abstract: Fertilization in agricultural peatlands accelerates nutrient cycling and creates a potential risk to nearby natural peatlands. Here, using undisturbed peatlands as reference, we studied soil carbon (C), nitrogen (N), phosphorus (P) and the key enzymes for nutrient cycling at 0–50 cm soil depth in agricultural, nearby disturbed peatlands in a temperate fen in Northeast China. Agricultural intervention significantly increased total P in agricultural and disturbed peatlands, and decreased soil organic carbon content and total N in surface soil of agricultural peatlands, however total N significantly accumulated at 20–30 cm soil both in agricultural and disturbed peatlands (p < 0.05). Both N-acetyl-β-glucosaminidase and phosphatase significantly declined in agricultural peatlands, while only phosphatase decreased in disturbed peatlands (p < 0.05), and linear regression models showed strong effects of changes of soil nutrient levels on enzyme activities. The ratios of β-D-glucosidase to N-acetyl-β-glucosaminidase and phosphatase markedly increased in agricultural peatlands and showed higher ratios in deeper soil of disturbed peatlands, suggesting relatively higher microbial demand for carbon. Nonmetric multidimensional scaling analysis showed that variations of enzyme activity and stoichiometry can be used to reveal agricultural disturbance, and further redundancy analysis identified that total P and SOC explained 38.3% and 8.3% of the variance. Overall, our findings show that microbial enzymatic activity and stoichiometry can be effective and sensitive indicators of agricultural intervention and nutrient changes in peatlands, which implies that they can be used in monitoring of future fertilization management strategies aimed at fostering more sustainable agriculture.